2010
DOI: 10.1055/s-0030-1258203
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Rhodium-Catalysed Conjugate Addition of Chiral Alkenylboronates Using Chiral Olefin Ligands

Abstract: The rhodium-catalysed addition of chiral alkenylboron reagents to prochiral a,b-unsaturated carbonyl acceptors are demonstrated to proceed under ligand control. The highest activities were obtained with chiral olefin ligands and the configuration of the new stereocentre can be predicted by using established models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Guided by our investigation of cationic gold allenylidene complexes,23 we targeted the gold γ,γ-(diphenyl)vinylcarbene/allylic cation complex ( E )-[(IPr)AuC(H)C(H)CPh 2 ] + OTf – [( E )- 5a ] for initial investigation (Scheme 2). The requisite gold (γ,γ-diphenyl)vinyl complex ( E )-(IPr)AuC(H)C(H)C(OMe)Ph 2 [( E )- 6a ] was synthesized in two steps from propargylic ether 7a via zirconium-catalyzed hydroboration27 followed by transmetallation of the resulting boronic ester ( E )- 8a with (IPr)AuCl (Scheme 2). 28 Treatment of ( E )- 6a with trimethylsilyl trifluoromethanesulfonate (TMSOTf) in CD 2 Cl 2 at –95 °C led to immediate (<1 min) formation of a bright orange/red solution that became colorless over the course of ∼10 s. 1 H NMR analysis of the resulting solution at –95 °C revealed formation of trimethylsilyl methyl ether (TMSOMe) in 92 ± 5% yield, which established that efficient ionization of ( E )- 6a had occurred, but no resonances were observed that could be attributed to ( E )- 5a .…”
Section: Resultsmentioning
confidence: 99%
“…Guided by our investigation of cationic gold allenylidene complexes,23 we targeted the gold γ,γ-(diphenyl)vinylcarbene/allylic cation complex ( E )-[(IPr)AuC(H)C(H)CPh 2 ] + OTf – [( E )- 5a ] for initial investigation (Scheme 2). The requisite gold (γ,γ-diphenyl)vinyl complex ( E )-(IPr)AuC(H)C(H)C(OMe)Ph 2 [( E )- 6a ] was synthesized in two steps from propargylic ether 7a via zirconium-catalyzed hydroboration27 followed by transmetallation of the resulting boronic ester ( E )- 8a with (IPr)AuCl (Scheme 2). 28 Treatment of ( E )- 6a with trimethylsilyl trifluoromethanesulfonate (TMSOTf) in CD 2 Cl 2 at –95 °C led to immediate (<1 min) formation of a bright orange/red solution that became colorless over the course of ∼10 s. 1 H NMR analysis of the resulting solution at –95 °C revealed formation of trimethylsilyl methyl ether (TMSOMe) in 92 ± 5% yield, which established that efficient ionization of ( E )- 6a had occurred, but no resonances were observed that could be attributed to ( E )- 5a .…”
Section: Resultsmentioning
confidence: 99%
“…threo - and erythro - 2 -1,2- d 2 were prepared by employing a modified version of the procedures reported by Morken and co-workers . Vinyl boronic esters ( E )- 6 and ( Z )- 6 were prepared by employing modified versions of the procedures reported by Frost et al . and Miyaura and co-workers, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…40 threo-and erythro-2-1,2-d 2 were prepared by employing a modified version of the procedures reported by Morken and co-workers. 41 Vinyl boronic esters (E)-6 and (Z)-6 were prepared by employing modified versions of the procedures reported by Frost et al 42 and Miyaura and co-workers, 43 respectively. (3-Bromo-1-methoxypropyl)benzene, 44 3-methylthio-3-phenyl-1propanol, 45 cis-1-chloro-3-methoxycyclohexane, 46 and 1-methoxy-1phenylpropyne 47 were prepared by employing known procedures.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…42 In the context of this chapter it shall also be mentioned that 340 recently a stereoselective rhodium-catalyzed ACA has been reported with a chiral nucleophile where diene ligand L4 was found to give the best diastereoselectivities which could be inverted by use of the other enantiomer of L4. 44 Various alkenylsilanes undergo cleanly Rh-catalyzed ACA to 400 give highly enantioenriched products (Scheme 23). 47 The methodology has also been successfully extended to β-silyl α,β- Despite, the reusability of the silicon source and the excellent results obtained it is less likely that this methodology will see many applications as the synthesis of the elaborate nucleophiles involves a 3-6 steps procedure which renders the methodology 410 less practical.…”
Section: Boron Nucleophilesmentioning
confidence: 99%
“…In the context of this chapter it shall also be mentioned that recently a stereoselective rhodium-catalyzed ACA has been reported with a chiral nucleophile where diene ligand L4 was found to give the best diastereoselectivities which could be inverted by use of the other enantiomer of L4. 44 Without the addition of ligand a 50 : 50 mixture of the two diastereoisomers was obtained (Scheme 19).…”
Section: Potassium Organotrifluoroboratesmentioning
confidence: 99%